Manual for Dental Hygienist - Awasthi, M. G. PN Maj Gen PN (Jaypee Brothers Medical Publishers, 2018)
The Manual for Dental Hygienist starts with the very basic lessons which are the essential foundation stones for the advanced learning of the complexities of understanding the periodontal disease and its presentation in the oral cavity. The chapters also cover detailed information on generating awareness, motivation for prevention and also the therapeutic measures both surgical and medical for the treatment of dental disease. The role of the dental hygienist has become an integral part of the overall treatment. Dental hygienist regulations according to Dental Council of India are appended at the end of book. The manual includes recent advancements in oral health care and code of ethics for dental hygienist. Divided in 7 sections, all 56 chapters have been written in a very simplified, concise pattern so that the contents can be easily grasped by the trainees and the trainers in dental practice.